2020
DOI: 10.1155/2020/9720387
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Ligularia fischeri and Aronia melanocarpa Extracts on Alcoholic Liver Disease (In Vitro and In Vivo Study)

Abstract: Hepatic protective effects of Ligularia fischeri (LF) and Aronia melanocarpa (AM) against alcohol were investigated in vitro and in vivo test. LF, AM, and those composed mixing material (LF+AM) were treated in HepG2 cell. Alcohol dehydrogenase (ADH) and acetaldehyde dehydrogenase (ALDH) activities were significantly increased in each singleness extract and mixed composite. The protective effect on alcoholic liver damage was investigated by animal models. Serum alcohol level and acetaldehyde level were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The lipid-containing bottom solutions were collected, and then, pellets were obtained by evaporating chloroform via centrifugation for 2 h using a centrifugal vacuum concentrator. Later, lipids were solubilized using chloroform, and then, hepatic triglyceride and total cholesterol were mea-sured using a quantitative measurement kit and followed according to the kit manufacturer's protocol [29].…”
Section: Measurement Of Serum Liver Damage Indices and Lipidmentioning
confidence: 99%
“…The lipid-containing bottom solutions were collected, and then, pellets were obtained by evaporating chloroform via centrifugation for 2 h using a centrifugal vacuum concentrator. Later, lipids were solubilized using chloroform, and then, hepatic triglyceride and total cholesterol were mea-sured using a quantitative measurement kit and followed according to the kit manufacturer's protocol [29].…”
Section: Measurement Of Serum Liver Damage Indices and Lipidmentioning
confidence: 99%
“…These concentrations of EtOH and AA are physiologically relevant ( Ferrier et al, 2006 ; Guillot et al, 2019 ). Plasma AA concentrations vary from 40 to 200 μM after chronic alcohol feeding ( Gao et al, 2019 ; Guillot et al, 2019 ; Hao et al, 2018 ; Shimoda et al, 2016 ), whereas 400–1,000 μM AA ( Han et al, 2019 ; Pyun et al, 2020 ) were recorded after acute alcohol administration. SOR-C13, a short peptide based on the amino acid sequence of the protein soricidin, is a specific inhibitor of TRPV6 ( Bowen et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is also related to elevated serum levels of CRP, tumor necrosis factor-α, interleukin (IL)-1β, and IL-6 [ 44 ]. Previous studies have demonstrated that Aronia and ginseng improve insulin resistance and NAFLD and reduce oxidative stress, inflammation [ 45 ], and alcohol-induced liver damage [ 46 ]. In the present study, AGM intake reduced the serum activities of γ-GT and ALT and serum CRP concentrations, which suggests AGM can reduce hepatic insulin resistance and inflammation.…”
Section: Discussionmentioning
confidence: 99%